Comparison of Dexmedetomidine Infusion versus Scalp Block with 0.5% Ropivacaine to Attenuate Hemodynamic Response to Skull Pin Insertion in Craniotomy: A Prospective, Randomized Controlled Trial - Singh, Georgene; Arimanikam, Ganesamoorthi; Lionel, Karen R.; Smita, V.; Yadav, Bijesh; Arulvelan, Appavoo; Sethuraman, Manikandan (Journal of Neuroanaesthesiology and Critical Care, 2020)
Background The insertion of the skull pin head holder to stabilize the head during neurosurgery causes significant periosteal stimulation, resulting in hemodynamic responses, which may lead to brain edema, intracranial hypertension, and hemorrhage in patients with intracranial space-occupying lesions and intracranial aneurysms. We compared the efficacy of dexmedetomidine infusion and 0.5% ropivacaine scalp block in attenuating the hemodynamic response to the skull pin application.Methods A total of 65 American Society of Anesthesiologists (ASA) class I and II patients aged between 18 and 65 years with a preoperative Glasgow Coma Scale score of 15 undergoing elective craniotomy were randomized to receive either a bolus of 1mcg/kg of dexmedetomidine followed by an infusion of 1 mcg/kg/hour (group D) or a scalp block with 0.5% ropivacaine (group S) in a single-blinded comparator study. Patients were monitored for the following hemodynamic changes following skull pin insertion: heart rate (HR), mean arterial pressure (MAP), the requirement of additional analgesia/anesthesia, and adverse events.Results HR and MAP were comparable between the groups at baseline, before induction, and before pin insertion. HR and MAP at 1, 2, and 3 minutes after skull pin insertion were significantly higher in group D as compared with group S (p < 0.05) and were comparable between the groups at 5 minutes. The groups were comparable with respect to the requirement of additional analgesia, anesthesia, and incidence of adverse events.Conclusion Scalp block with 0.5% ropivacaine is effective and superior to dexmedetomidine in attenuating the hemodynamic response to skull pin insertion in ASA I and II neurosurgical patients undergoing craniotomy. However, the hemodynamic effects achieved with dexmedetomidine were within the permissible limits.
Keywords: ropivacaine; scalp block; dexmedetomidine; hemodynamic response